Compatibilidad in vitro para prevenir reacciones adversas a la transfusion cuando se administra paquetes globulares que contengan variedad de carga antigénica del sistema rh, mediante ensayos realizados a muestras de sangre de usarios atendidos en el servicio de medicina transfusional del hospital general docente de riobamba, durante el periodo marzo – agosto del año 2013 - Villacrés, Lisseth (2013)
This researching work describes fundamentally the topic "Compatibility in vitro to prevent transfusion reactions when administered globular packages containing antigenic load range Rh blood samples of users served in the Transfusion Medicine Service General Hospital Riobamba during the period March-August 2013 " it has vital importance in the field of transfusion medicine , the purpose of compatibility testing is to ensure , as far as possible that the donor's blood will not cause no adverse reaction in the receptor person. These tests are carried out facing the donor's red cells containing antigens with serum containing antibodies to the receptor person, if the recipient's serum had an antibody directed against an antigen of red blood agglutination was observed .